Adverse Childhood Experiences Are Associated With Adult Dream Content: A Cross-Sectional Survey - Ma, Yundong; Feng, Xia; Wang, Di; Zhao, Xiaoxia; Yan, Zejun; Bao, Yanping; Zhu, Ran; Sun, Qiqing; Deng, Jiahui; Lu, Lin; Sun, Hongqiang (Frontiers in Psychology, 2022)
Background Dreams can be affected by recent life events and long-term life experiences. Previous evidence has shown that childhood adverse experiences are associated with sleep quality and dream experiences. Objective The aim of this study was to explore the relationship between childhood adverse experiences and dream content in adults. Participants and Setting A total of 163 participants without current or past physical or mental disorders aged between 18 and 35 were screened in the hospital. Among them, 120 subjects who completed a dream content record at home and whose anxiety and depression levels and sleep quality were within the normal range were included in the data analysis. Methods A cross-sectional survey was conducted from June 2017 to December 2019. Dream content for 10 consecutive days was recorded by the participants and coded by the Hall and Van de Castle coding system. Childhood adversity was assessed by the Childhood Trauma Questionnaire (CTQ). In the end, 719 dreams out of 626 nights for 120 participants (44 female) were included in the data analysis, gender differences between groups were analyzed using t-tests or U tests, and Spearman’s partial correlation and multiple linear regression were used to investigate the relationship between childhood trauma and dream content. Results Childhood adversity was associated with characters, friendly interactions, and objects in dream content. Regression models of childhood adversity predicting characters and objects in dream content were constructed. There were no gender differences in general demographic data, sleep quality, emotional state, childhood adversity, dream recall frequency, or dream content. Conclusion Childhood adversity is associated with adult dream content.